2020
DOI: 10.18357/ijcyfs111202019473
|View full text |Cite
|
Sign up to set email alerts
|

Popularity, Gender, and Social Inclusion Among Girls in Ethnically Diverse Contexts in Norway

Abstract: This article discusses the phenomenon of popularity and its implications for gender construction, social inclusion, and gender equality among girls in two ethnically diverse contexts in Norway. At one field site, girls of immigrant origin were a majority, at the other they were a minority. Based on detailed ethnographic methodology and participant observation over time, this study shows that the crucial dimensions of popularity overlap with “economies of dignity” and vary according to whether the ethnic Norweg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…It has previously been concluded that affluence may be especially central for girls’ social status and popularity as they seek to stay in touch with the latest fashions [ 19 , 30 , 33 ]. Rysst [ 48 ] concluded that popularity among girls is connected to consumption, which may have negative consequences for immigrant girls because they often live in low-income families.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been concluded that affluence may be especially central for girls’ social status and popularity as they seek to stay in touch with the latest fashions [ 19 , 30 , 33 ]. Rysst [ 48 ] concluded that popularity among girls is connected to consumption, which may have negative consequences for immigrant girls because they often live in low-income families.…”
Section: Discussionmentioning
confidence: 99%
“…Det kan likevel vaere problematisk at et slikt budskap leses utfra influensermarkedsføring. Tidligere studier viser at når forbruksvarer fungerer som statusmarkører, så kan de brukes for å signalisere popularitet blant norsk ungdom (Rysst, 2020). Ifølge Daloz (2010) kan det å vise frem eksklusive produkter for å signalisere sosial status vaere viktig for enkelte som bor i et samfunn som produserer overskudd.…”
Section: Diskusjonunclassified
“…However, "particular goods and experiences" that are "suddenly…fraught with meaning" are not easy to grasp for an outsider or researcher, and often demand a bottom-up methodology that includes long-time participant observation. In my experience, the distinctions in the hierarchies of children and youth are seldom revealed through interviews only (Rysst, 2020(Rysst, , 2022.…”
mentioning
confidence: 92%